Computational study of diffusivities in diamond Ge-Si alloys - Cui S.L.; Zhang L.J.; Zhang W.B.; Du Y.; Xu H.H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A variety of diffusivities in Ge-Si alloys available in the literature were critically reviewed. On the basis of the critically reviewed literature data, the diffusion parameters for self diffusivities and impurity diffusivities in diamond Ge-Si alloys were determined by considering the diffusion mechanism. A phenomenological treatment of the diffusivities in Ge-Si alloys were conducted. The finally obtained atomic mobilities can reproduce most of the diffusivities in diamond Ge-Si alloys as well as the concentration profiles of Ge-Si binary diffusion couples. In addition, the Manning modification on Darken Equation in diamond structure was also tested by using the presently obtained atomic mobilities.